A novel piezoelectric energy harvester of noncontact magnetic force for a vehicle suspension system - Zhen Zhao; Baifu Zhang; Yongxin Li; Chunjiang Bao; Tie Wang (Energy Science & Engineering, 2023)
Abstract The vehicle suspension system is considered to have tremendous potential in energy harvesting and to be applicable for improving the efficiency of energy use of the vehicle. A novel piezoelectric energy harvester (PEH) with noncontact magnetic force has the feature of low friction loss and is designed based on the vibration characteristic of the suspension system. The research comprises two main components: the motion conversion component and the energy conversion component. A screw‐nut mechanism that can convert linear vibration between the vehicle body and the wheel into rotational motion is used as the motion conversion component. The energy conversion component is a core component of the PEH; its function is to convert rotational energy into electrical energy through noncontact magnetic force and piezoelectric effect. The magnetic excitation model's credibility and the modeling method's feasibility are verified by experiment and simulation. Through vehicle field tests, the influence of the driving speed, road surface roughness, and cargo state on the harvested power is obtained. Driving on a random road, the maximum of the generated power is 24.28 W, at 60 km/h, under the laden state. Driving on a pulse road, the harvested power is 3346 W, at 30 km/h, under the unladen state. It is indicated that the PEH is a promising and practical option for harvesting energy for the vehicle's suspension system.